Coinfection of disseminated Talaromyces marneffei and Mycobacteria kansasii in a patient with papillary thyroid cancer: A case report. Issue 52 (December 2017) - Zhang, Jing; Huang, Xinyan; Zhang, Xin; Zhu, Ying; Liao, Kang; Ma, Jing; Wang, Guangfa; Guo, Yubiao; Xie, Canmao
Abstract: Rationale: Recently, Talaromyces marneffei ( T. marneffei ) has been reported in human immunodeficiency virus (HIV)-negative patient with underlying diseases, such as oral cancer, colon cancer, haematological malignancies, connective tissue disease, diabetes mellitus, and corticosteroids or immunosuppressive agents. Similar to HIV-positive ones, such patients were observed with CD4 lymphocytopenia. Patient concerns: We reported a case of a 45-year-old woman who was diagnosed with disseminated T. marneffei and Mycobacteria kansasii ( M. kansasii ) with papillary thyroid cancer as the underlying disease. T-cell subsets counts, CD4 T-cell%, CD8 T-cell%, CD4/CD8 ratio, and NK cell% were all turned out to be normal. Diagnoses: Based on bronchoalveolar lavage fluid and skin lesions secretion cultures, blood culture, the patient was diagnosed with disseminated T. marneffei and M. kansasii . Pathological examination reported papillary thyroid cancer with cervical lymph node metastasis. Interventions: The patient received the combined and longer antifungal therapy and drug regimens for M. kansasii . She had total thyroidectomy with radical neck dissection to treat the papillary thyroid cancer. Outcomes: The patient had a favorable outcome for 19 months without recurrence. Lessons: T. marneffei could infect non-HIV individuals with underlying disease under the condition of normal T-cell counts. The symptoms were lack of specificity and were more likely to be misdiagnosed. Such patients with unidentified T-cell dysfunction or other unidentified primary immunodeficiency disorders may prone to coinfect with other opportunistic pathogens, such as M. kansasii . Compared with HIV-positive ones, they need combined and much longer antifungal therapy.